2003
DOI: 10.1007/s00415-003-1302-y
|View full text |Cite
|
Sign up to set email alerts
|

Familial Parkinson?s disease: a hint to elucidate the mechanisms of nigral degeneration

Abstract: In the majority of patients with Parkinson's disease (PD), it is now clear that genetic factors contribute to the pathogenesis of PD, although the contribution of genetic and environmental factors remains to be elucidated. The contribution of genetic factors to the pathogenesis of PD is supported by the demonstration of the high concordance in twins, increased risk among relatives of PD patients in case control and family studies, and the existence of familial PD based on single gene defects. Recently, several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 84 publications
(93 reference statements)
1
12
0
Order By: Relevance
“…This is consistent with previous studies that have found reduced mitochondrial [13][14][15] and UPS [16] activity in the Parkinsonian brain. Our findings are also in line with studies of familial PD [41][42][43] and work on animal models of PD [44][45][46], which have independently implicated both metabolic systems in PD. For the first time, it is shown here that the two systems are functionally linked in the human brain.…”
Section: Regulation Of Mitochondrial and Ubiquitin-proteasome Gene Exsupporting
confidence: 91%
“…This is consistent with previous studies that have found reduced mitochondrial [13][14][15] and UPS [16] activity in the Parkinsonian brain. Our findings are also in line with studies of familial PD [41][42][43] and work on animal models of PD [44][45][46], which have independently implicated both metabolic systems in PD. For the first time, it is shown here that the two systems are functionally linked in the human brain.…”
Section: Regulation Of Mitochondrial and Ubiquitin-proteasome Gene Exsupporting
confidence: 91%
“…There is evidence that genetic factors play a key role in the development of PD. Studies of twins have provided strong evidence for an important role of environmental factors in the aetiology of typical PD [3,4]. The development of PD involves an interaction between genes and environmental factors.…”
Section: Financial Disclosures Concerning the Research Related To Thementioning
confidence: 98%
“…Among these, PARK2 encodes a RING domain-containing E3 ubiquitin ligase that is widely expressed throughout the nervous system but whose cellular function is poorly understood (1,(12)(13)(14)(15)(16)(17). Among the reported substrates of parkin are several proteins implicated in synaptic transmission, including CDCrel-1 (15), glycosylated ␣-synuclein, synphilin, synaptotagmin XI (18), Eps15 (19), and protein interacting with C kinase 1 (20).…”
Section: Mutations In the Park2 Gene Cause Hereditary Parkinson Diseamentioning
confidence: 99%